Determinants of top-tier banking efficiency in Europe : size and ownership - Machado, André Cordeiro Costa (2020)
The present Dissertation’s research focus is the measurement of the relative efficiency of top-tier commercial banks and the evaluation of its determinants, in the context of the European banking markets, for 2017 and 2018. Particularly, the main determinants under study are the size of banks and their ownership types, namely foreign and government ownership. In order to do so, the methodology employed follows the two-step Double-Bootstrap Truncated Regression model. In the first step, the Data Envelopment Analysis is utilized in order to obtain the banks’ efficiency scores. The Malmquist Productivity Index is also implemented in order to provide robustness and complement the first-stage results. Subsequently, in the second step, a Double Bootstrapped Truncated Regression is applied, originating bias-corrected regression coefficients, while examining how the variables under study affect the banks' efficiency levels. The results obtained indicate that there is a positive and significant relationship between banks’ size and their overall level of efficiency, a result in line with the majority of the academic literature. The variable representing foreign ownership is found to have a positive and significant relationship with efficiency levels (only for 2018), whereas the one representing state ownership shows a negative significant relationship with efficiency. The present Dissertation thus contributes to the academic literature by confirming the general acceptance that size does affect bank efficiency positively and by providing further insight to the non-consensual study of the relationship between ownership types and bank efficiency.